PERCOBAAN PEMBUATAN LAK KUNING DENGAN PROSES PELARUTAN - Abdul Hakim Lukman; Toga Silitonga (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
Shellac can be produced by two different procedures, namely heat process and solvent process: Ordinarily, domestic shellac produced by heat process, while imported one (from India) by solvent process. Solvent process yields shellac much purer than heat processed, with relatively better properties.The physicochemical properties of shellac produced in this experiment, i.e.: moisture content 2. 36%, ash content 0.15%, matter soluble in water 0.43%, matter soluble in cold alcohol 97.86%, acid number 46.81 and Iod number 16.39. Shellac from fabric manufacturing have its properties i.e.: moisture content 4.03%, ash content 0.27%, matter soluble in water 3.26%, matter soluble in cold alcohol 89.14%, acid number 41.01 and Iod number 31.35.Result of LSD test between experiment shellac and shellac from fabric are reveal highly significant different for ash content, matter soluble in water, matter soluble in cold alcohol and Iod number, but is not significantly different for the other properties.